Belonging - Unerman, Sue; Jacob, Kathryn; Edwards, Mark (Ascent Audio, 2021)
There's never been more discussion around diversity and inclusion in the workplace. From gender pay gaps to the #MeToo movement, it seems that every organization has finally recognized that change needs to happen. Despite this, true progress towards more inclusive workspaces has been excruciatingly slow and, in some cases, has grinded to a halt. Following extensive research and interviews at over 200 international businesses, Kathryn Jacob, Sue Unerman, and Mark Edwards have discovered the major problem that is holding back the move towards greater diversity: where are all the men? Most men are not engaged with DI initiatives in the workplace-at one extreme they may be feeling actively hostile and threatened by the changing cultural landscape. But others may be unmotivated to change-recognizing the abstract benefits of diversity but not realizing what's in it for them. Built upon this seemingly counterintuitive approach of bringing men into the conversation, Belonging is an accessible and comprehensive guide to achieving diversity that lasts.